Epiplating in auricular defects as a facial reconstruction method: case series (2019)
The aim of this study is to report on the use of the Epiplating system (Medicon, Tuttlingen, Germany) for the management of craniofacial deformities for optimal functional and esthetic facial reconstruction. The present series of cases comprises 3 patients diagnosed with congenital auricular agenesis who required correction of the auricular defect with osseointegrated implants from the Epiplating system. The implants were left to integrate for a period of 2 to 12 weeks, followed by placement of an implant-retained prosthesis. The criteria for success of the prosthesis include overall stability and function, symmetry, position, and patient acceptance. The implants achieved anchorage, and none showed failure during the study period. The cosmetic results and patient acceptance were very satisfactory, with no postoperative and/ or soft tissue complications. Therefore, the survival rate was 100%. This study concludes that the Epiplating system allows optimal functional and esthetic facial reconstruction for the management of craniofacial deformities, as the combination of art and science allows individualized adaptations to improve the quality of life of patients